The Ethics of Entrepreneurial Shared Value - Osorio-Vega, Patricio (Journal of Business Ethics, 2019)
In the business ethics literature, the growing interest in social entrepreneurship has remained limited to the assumption that pursuing a social mission will clash against the pursuit of associated economic achievements. This ignores recent developments in the social entrepreneurship literature which show that social missions and economic achievement can also have a mutually constitutive relation. We address this gap adopting the notion of shared value (SV) for an ethical inquiry of social entrepreneurship. Using a sensemaking framework, we assume that the emergence of SV propositions can be captured through the analysis of how social entrepreneurs make sense of events of change, selecting the journey of three exemplar cases for an inductive empirical inquiry. From our findings, we propose three themes for further examination. First, the ethical groundings of entrepreneurial SV are mostly shaped by idiosyncratic imperatives that inform both social mission and economic gain from the onset. Second, the ethical groundings of entrepreneurial SV will be likely operationalised as a filtering device, which allows for resilience as well as potentially detrimental blind spots. And third, the ethical groundings of entrepreneurial SV are expressed through ongoing transparency. Whilst there are agendas, these are not necessarily hidden but instead are likely put on show for the scrutiny of markets and communities. We hope that this evidence can add more light to our still modest understanding of the ethical groundings of social entrepreneurship.
Keywords: Réservé UdeM